Relasi Modalitas Penerimaan Informasi (Visual, Auditori, Kinestetik) terhadap Nilai Geografi Siswa SMA (Studi Kasus Siswa Kelas XI SMAN 3 Gorontalo) - Is Igirisa; Julisa Tryansah Gobel; Dina Aprilia Y; Sri Amelia Akase; Masril Baki; Masruroh Masruroh (Jurnal Pendidikan Geografi Undiksha, 2026)
This research is motivated by the importance of understanding information acquisition modalities (VAK) as a factor that can affect students' learning outcomes in geography subjects at the secondary school level. The purpose of this study is to analyze the tendency to receive information (VAK) of grade XI students at SMAN 3 Gorontalo and its relationship with geography learning outcomes. This study uses a descriptive quantitative approach by collecting data through an information receipt questionnaire (VAK) and documentation of geographic values. The results showed that auditory information reception was the most dominant, followed by visual and kinesthetic information reception. The results of correlation and regression analysis showed that the relationship between the information reception modality (AVK) and the Geography value was not statistically significant, with the contribution of the information reception modality (AVK) only 1.3%. These findings show that the information reception modality (AVK) is not the main factor that directly determines the achievement of Geography learning outcomes, but there are other factors that are more dominant However, this finding emphasizes the importance of implementing adaptive learning strategies so that differences in students' information reception modalities can be optimally accommodated.